Methodological approaches in testing maximal lactate accumulation rate - vLamax: A systematic review - Langley, J.; Haase, R.; Nitzsche, N.; Porter, M. (Journal of Science and Cycling, 2025)
In 1984 Mader constructed a mathematical model of human energy metabolism to understand the metabolic origin behind the maximal lactate steady state. An integral parameter of Mader`s model requires knowledge of the maximal rate of glycolysis, which Mader derived from the maximal lactate formation rate within the muscle cell. However, in-vivo the maximal lactate formation rate within the muscle cannot be measured. Subsequently, Mader proposed the utility of measuring the rate of maximal blood lactate accumulation following supramaximal exercise as an indirect measure of glycolytic flux, termed vLamax. Recently, the vLamax has gained popularity amongst researchers and practitioners as an indirect assessment method to determine the maximal glycolytic rate. Currently, there is a distinct lack of continuity in methodological approaches between researchers. Therefore, the primary aim of this systematic review was to evaluate the current methodological approaches applied to test the vLamax. Based on the findings we make practical recommendations for researchers to adopt to promote standardisation of test procedures. Comprehensive searches of the databases; PubMed, SCOPUS, Google Scholar, and SPOLIT, identified 3545 articles for screening (1984-2024). In total 27 articles were included within this review, with seven different modalities identified. The results from this systematic review highlight several key considerations which need to be considered when testing the vLamax including; alactic timespan, test duration, baseline blood lactate concentration, modality specificity, movement velocity, recovery procedures, and post exercise blood lactate sampling times. Based on these findings this review provides detailed recommendations to standardise vLamax methods considering pre-test, test, and post-test factors.